Immigration Intelligence and Counterterrorism Strategies in Indonesia - Heniarti, Dini Dewi; Fernando, Zico Junius; Kusumah, Fardana (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2025)
The background of this study is the increasing volume of international human mobility, which presents serious challenges for Indonesia’s immigration system in preventing terrorism and maintaining state security. The Directorate General of Immigration struggles with outdated infrastructure, limited technological support, and insufficient human resource capabilities, all of which hinder effective immigration checks and the identification of high-risk individuals. Terrorists have exploited loopholes in Indonesia’s immigration system to enter or flee the country. The purpose of this research is to investigate whether the immigration intelligence approach can serve as an effective and comprehensive strategy for combating terrorism in Indonesia. The method employed in this study is qualitative, involving library research that analyses secondary sources, including legislation, case studies (e.g., the 2016 Sarinah attack and the 2018 Surabaya bombing), government reports, and scholarly literature. The results obtained indicate that immigration intelligence through mechanisms such as risk profiling, early detection, inter-agency collaboration, and technological integration plays a crucial role in identifying and preventing terrorist threats before they occur. Conclusions that can be drawn from this study are that immigration intelligence offers significant preventive advantages but requires strengthened infrastructure, improved coordination among institutions, and international cooperation to be fully effective in Indonesia’s counterterrorism efforts.